Implementation of the Snowball Throwing Learning Model to Increase Students' Understanding of Appreciating Equality of Citizens in Class X Accounting at SMK Negeri 1 Kutacane - Dhimas Arya Bima; Ulian Barus (International Journal of Educational Research Excellence (IJERE), 2023)
This study aims to determine the increase in students' understanding in respecting the equality of citizens. The subjects in this study were class X ACCOUNTING students at SMK NEGERI I KUTACANE consisting of 20 students in one class of boys and girls. This research was conducted using classroom action research (CAR), which consisted of four stages: planning, action, observation, and reflection. The data analysis technique used in this research is quantitative. Quantitative data obtained from cycle I and cycle II tests. The data were analyzed from cycle I and cycle II. The results showed that there was an increase in students' abilities in direct learning, this showed that the average value of the first cycle was 76 and the second cycle score was 79.5.